Let's address each part of your request step-by-step.
1. Transform the linear equation \(4x - 8y = 24\) to slope-intercept form.
The slope-intercept form of a linear equation is given by \(y = mx + b\), where \(m\) is the slope and \(b\) is the y-intercept.
Starting with the equation: \[ 4x - 8y = 24 \]
First, isolate \(y\): \[ -8y = -4x + 24 \]
Now, divide every term by \(-8\): \[ y = \frac{1}{2}x - 3 \]
Thus, the slope-intercept form is: \[ y = \frac{1}{2}x - 3 \]
2. Write \(y - 2 = \frac{3}{2}(x + 2)\) in slope-intercept form.
Start with the equation: \[ y - 2 = \frac{3}{2}(x + 2) \]
Distribute \(\frac{3}{2}\) on the right side: \[ y - 2 = \frac{3}{2}x + 3 \]
Now, add \(2\) to both sides to solve for \(y\): \[ y = \frac{3}{2}x + 3 + 2 \] \[ y = \frac{3}{2}x + 5 \]
Thus, the slope-intercept form is: \[ y = \frac{3}{2}x + 5 \]
3. Graph the equation \(9 - x = \frac{3}{2}y\) using slope-intercept form.
Start with the equation: \[ 9 - x = \frac{3}{2}y \]
Rearranging to isolate \(y\): \[ \frac{3}{2}y = 9 - x \]
Multiply through by \(\frac{2}{3}\): \[ y = \frac{2}{3}(9 - x) \] \[ y = 6 - \frac{2}{3}x \]
Now, the slope-intercept form is: \[ y = -\frac{2}{3}x + 6 \]
Graphing the Equation
To graph \(y = -\frac{2}{3}x + 6\):
- Identify the y-intercept: \(b = 6\). This is the point \((0, 6)\) on the y-axis.
- Identify the slope: \(m = -\frac{2}{3}\). This means for every 3 units you move to the right (positive x-direction), you move down 2 units (negative y-direction).
Plotting the points:
- Start at the y-intercept \((0, 6)\).
- From \((0, 6)\), move 3 units to the right to \((3, 6)\) and then down 2 units to the point \((3, 4)\).
- Draw a straight line through these points, extending it in both directions.
Now you've transformed the equations and know how to graph the last one!